Technical university students’ feedback on studying English online under the COVID-19 - Oksana Chugai; Larysa Svyrydova (Multidisciplinary Journal for Education, Social and Technological Sciences)
The paper reveals the results of the survey, carried out by non-linguistic students of National Technical University of Ukraine “Igor Sikorsky Kyiv Polytechnic Institute”. Special attention is devoted to comparative analysis of feedback of respondents studying English online at the Institute of Physics and Technology (IPT) and Instrumentation Engineering Faculty (IEF) under the COVID-19. The actuality of the study is determined by the necessity of learning about students` experience studying English online during the 2020-2021 academic year for educators to design effective online courses and strategies, adjust teaching practices according to students’ needs. To achieve the aim, the following tasks were completed: first of all, to establish technical aspects of students’ learning experience, their attitudes to grouping, interactive activities, tests, English lessons online in general, and then to use descriptive statistics for processing the obtained data. The results of the survey are analyzed, described, and presented. Overall, the respondents positively assessed their experience of studying English online under the COVID-19.